Solvency Resilience Analysis Using Dynamic Financial Analysis:A Simulation of Adaptive Asset Allocation at PT Asuransi Bina Dana Arta Tbk - Aurellia Aknesia Hendrawan; Sindi Pratika Siwi; Fikri Haikal; Putri Najwa Minadhifa (CV. Multimedia Teknologi Kreatif, 2026)
This research aims to evaluate the solvency resilience of PT Asuransi Bina Dana Arta Tbk (ABDA) against catastrophic shocks and investment market volatility through a System Dynamics simulation approach within a Dynamic Financial Analysis (DFA) framework, addressing the limitations of prior static methods that fail to capture dynamic management responses. Utilizing Q1 2025 financial data projected over a 60-month horizon, this study tests a double stress test scenario comprising a 350% surge in claims and a simultaneous stock market correction to measure the effectiveness of adaptive asset allocation policies. The simulation results demonstrate that the company's capital structure is highly robust, with the Risk-Based Capital (RBC) ratio remaining above 200% under normal conditions, and despite experiencing severe pressure in the crisis scenario, the lowest solvency level (nadir point) reached was 150.64%, which remains significantly above the Financial Services Authority (OJK) regulatory threshold of 120%. These findings conclude that the company possesses resilient fundamentals, where the implementation of an automated de-risking mechanism proved to be a crucial factor in preventing insolvency and mitigating capital erosion during economic turbulence, suggesting that dynamic approaches should be adopted as a new standard in insurance risk management.